Volume 2D: Turbomachinery 2014
DOI: 10.1115/gt2014-25641
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Impeller Tip Tailoring and its Impact on Aerodynamic Design of a Centrifugal Compressor’s Impeller

Abstract: The current research focuses on the aerodynamic design of a centrifugal compressor and the effect of tip tailoring on the aerodynamic impeller efficiency. To this extent a high-fidelity multi-point design optimization process has been developed and exploited on a high pressure ratio transonic impeller. By manipulating the shape of the impeller blades and endwalls and by including advanced geometrical features such as winglets on the impeller blades, the behavior of the impeller flow has been investigated. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The recessed tips were also effective in reducing the tip leakage flow. Recently Mahajan et al [16] had carried out computations on a transonic centrifugal compressor with a winglet on the suction side of the impeller blade near its tip. They had shown that the isentropic efficiency of the impeller with winglet was improved compared to the reference impeller.…”
Section: Introductionmentioning
confidence: 99%
“…The recessed tips were also effective in reducing the tip leakage flow. Recently Mahajan et al [16] had carried out computations on a transonic centrifugal compressor with a winglet on the suction side of the impeller blade near its tip. They had shown that the isentropic efficiency of the impeller with winglet was improved compared to the reference impeller.…”
Section: Introductionmentioning
confidence: 99%